In vivo study of implanted aortic scaffolds decelluraized by sonication treatment - Noor Azmi, Azran Azhim; N. , Syazwani; Y. , Morimoto; K.S. , Furukawa; T. , Ushida (2013)
Sonication treatment is used in the preparation of scaffold that elicitsminimal immune response after implantation. The aim of this study is to investigate the immunologic responseof sonicatedly decellularizedaortic scaffoldsafter 7 and 35 days of subcutaneousimplantation. In this study, aorta samples weresonicatedly decellularized in0.1% and 2% SDS detergentfor 10 hours. It wasfollowed by washing process withPBS solution for 5 days. The treated samples were then evaluated histologically by Hematoxylin Eosin (HE) stainingand DNA quantification. The samples were subcutaneously implanted on the lower right thoracic cavity ofWistar rats. The implants were explanted and evaluated by HE staining. From the histological results, the implanted samples after sonicatedly decellularized with 2% SDS shows minimal immune response,compared to that decellularized with 0.1% SDS detergents. Hence, sonicatedly decellularized scaffolds treated with 2% SDS showedgreat potential as future biomedical implants.